Game Based Learning Interactive Multimedia in Improving Thematic Learning Achievement of Third Grade Students - Sukmana, Adrianus I Wayan Ilia Yuda; Permana, Ahma Akbar; Sudatha, I Gde Wawan (Universitas Pendidikan Ganesha, 2023)
The problem with thematic learning is that the teacher only uses the lecture method without involving learning media. It shows the low use of learning media in schools so that student achievement decreases. This study aims to develop interactive multimedia learning media based on game-based learning in the Thematic Theme 5 learning for third-grade elementary school students. The research subjects comprised one subject matter expert, one design expert, one media expert, and product trial results from 12 students. This research is research development (Research and Development) using the ADDIE model. The methods used for data collection are observation, interviews, and questionnaires. Technical analysis of data using qualitative and quantitative analysis. Based on the assessment of learning content experts who obtained review results, namely 96.25% with the qualification very good, learning design experts obtained review results, namely 93.33%, learning media experts obtained review results, namely 94.67%, individual test, namely 97 .78% and the small group test is 97.63% with very good qualifications. Thus, interactive multimedia based on game-based learning in thematic learning theme 5 is appropriate for use in teaching and learning activities to build student enthusiasm in participating in the learning process. This research implies that interactive multimedia is a learning medium that helps understand the material.